2012
DOI: 10.1109/tmag.2012.2197814
|View full text |Cite
|
Sign up to set email alerts
|

Surface Roughness Reduction in $L 1_{0}$ Ordered FePd Alloy Thin Films Formed on MgO Single-Crystal Substrates with Different Orientations

Abstract: ordered FePd alloy epitaxial thin films are prepared on MgO substrates of (001), (110), and (111) orientations by two different methods; by direct deposition at high temperature of 600 C and by preparation of film at a low temperature of 200 C followed by high temperature annealing at 600 C. The influence of preparation method on film structure, order degree, surface roughness, and magnetic property are investigated. Films with ordered structure grow epitaxially on MgO substrates when deposited at 600 C. Epita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 7 publications
1
11
0
Order By: Relevance
“…Similar results on the variant configurations and the order degrees are confirmed for the magnetic materials of 40 nm thickness prepared by employing a two-step process which consists of low temperature deposition at 200 °C followed by high temperature annealing at 600 °C 153,177) . When the magnetic materials were deposited at 200 °C, the films grew epitaxially with the disordered A1 structure.…”
Section: Methodssupporting
confidence: 72%
See 1 more Smart Citation
“…Similar results on the variant configurations and the order degrees are confirmed for the magnetic materials of 40 nm thickness prepared by employing a two-step process which consists of low temperature deposition at 200 °C followed by high temperature annealing at 600 °C 153,177) . When the magnetic materials were deposited at 200 °C, the films grew epitaxially with the disordered A1 structure.…”
Section: Methodssupporting
confidence: 72%
“…Considering that the film morphology is influenced during the film deposition process, a two-step process technique consisting of a low temperature film deposition followed by a high temperature annealing for L10 ordering has been investigated to prepare an L10 ordered film with improved surface flatness 153,174,175,177) . Figure 20 compares the surface structures of FePd thin films of 2 -40 nm thicknesses observed by atomic force microscopy (AFM).…”
Section: Methodsmentioning
confidence: 99%
“…The base pressures were lower than 4 × 10 -7 Pa. The detail of sample preparation is reported in our previous paper [6]. FePd films of 40 nm thickness were deposited on MgO(001) substrates at 200 ºC.…”
Section: Methodsmentioning
confidence: 99%
“…%) alloy epitaxial thin films with very flat surfaces, which are obtained on MgO(001) singlecrystal substrates by employing a two-step process; lowtemperature deposition at 200 ºC followed by hightemperature annealing at 400 ºC [6]. Very flat surface is required in FMR measurements to evaluate intrinsic magnetic relaxation in order to avoid extrinsic effect by surface roughness [7].…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] The authors have shown that a twostep process consisting of low temperature film formation followed by high temperature annealing is effective for the preparation of L1 0 -FePt thin film with an improved surface flatness. 6,7 When an Fe-Pt alloy thin film is formed on an oxide substrate such as MgO(001) single-crystal at low temperatures where the impinging atom migration is limited, the film morphology tends to be continuous with small surface undulations. By heating the film at a higher temperature, migration of atoms within the film proceeds to form an L1 0 -ordered structure keeping the film morphology.…”
Section: Introductionmentioning
confidence: 99%